Membangun Keterampilan Berbahasa Produktif: Tips untuk Mahir Berkomunikasi Secara Lisan dan Tertulis - Lubis, Wahyuni; Azizah, Nurul; Manurung, Marshanda; Sitepu, Miyana Dewi E; Maha, Nazwa Desilhan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article discusses the importance of developing productive language skills, namely speaking and writing, for effective communication. The main focus is on strategies to improve vocabulary, sentence structure, and self-confidence in communication. The methods used in this research are literature study and observation. The findings show that consistent practice, understanding sentence structure, and mastering vocabulary support the mastery of productive language skills. Barriers such as limited vocabulary and lack of self-confidence can be overcome through structured practice and constructive feedback. Technology and social media also influence productive language skills, especially in formal contexts. With the right approach, productive language skills can enhance communication in various aspects of life.